Power-Sharing in the English Lowlands? Exploring Farmer Cooperation and Participation in Water Governance - Whaley, Luke (Cranfield University, 2014)
Involving stakeholders in water governance is becoming an increasingly important topic in England. In this thesis I consider this ambition from the farming perspective, by investigating the potential for farmers to cooperate and participate in water governance. This dynamic is viewed through the conceptual lens of adaptive comanagement, an approach which its proponents claim can achieve the dual focus of ecosystem protection and livelihood sustainability under conditions of change and uncertainty. The relevance of adaptive comanagement is highlighted by the increasing complexity and uncertainty surrounding water governance in England, amongst other things because of the effects of climate change and a growing population. The research adopts an integrated methodological approach that revolves around a “politicised” version of the Institutional Analysis and Development (IAD) Framework. Initially, three separate analyses investigate the context surrounding farming and water governance. The results of the contextual phase are incorporated into a more focused analysis, involving five farmer irrigator groups in the lowlands of eastern England. Here the intention is to explore the broader issues the research raises by investigating the potential for these groups to comanage water resources. Nine factors of success are identified, from which deeper, more abstract causal mechanisms are inferred. The relevance of the findings are discussed in relation to farming and water governance in England going forwards. Several key outcomes emerge from this research, including: 1) a theoretical and practical demonstration of the applicability of the politicised IAD Framework to studies of adaptive comanagement, 2) an understanding of the ways in which power, policy, and levels of trust influence the ability of lowland farmers to cooperate and participate in water governance, 3) specific strategies that can be used to develop comanagement arrangements between farmer groups and water managers.
Keywords: Water governance; adaptive comanagement; farming; power; lowland England